Authenticity in cultural built heritage: learning from Chinese Indonesians' houses. Issue 2 (14th June 2019) - Februandari, Asmarani
Abstract : Purpose: The purpose of this paper is to explore authenticity conception of cultural built heritage. As a core of heritage management, authenticity is often seen as a validation of certain identity. In the cultural built heritage context, authenticity is vital for the community, particularly the ethnic minority community, because it can be viewed as a tool to tackle discrimination and misrecognition issues. Design/methodology/approach: This research was conducted in two Indonesian Chinatowns, namely, Lasem and Semarang Chinatowns. An ethnography method was employed to address the research aim. Four techniques to carry out data collection were used in this research; they were life story interview, participant observation, documentary research and physical observation through house tour. Two theories were used to analyse the data, and they were Technologies of the Self from Foucault and Habitus from Bourdieu. Findings: Result shows that authenticity conception in cultural built heritage is not fixed because it lies on the immaterial aspect (the community's cultural values) that is continuously reinvented. This research also reveals that the immaterial aspect of cultural built heritage, the community's cultural values, becomes the core of the conception of authenticity. These cultural values become the foundation for the community to create their cultural built environment. Social implications: This research brings an important perspective on authenticity to be applied in heritage management. Interestingly, by adopting this perspective, heritage management could become a tool to create an inclusive society. Originality/value: This research offers a unique perspective on heritage authenticity, which was constructed through sociological and materiality approach.